O recurso a procedimentos de auditoria financeira no combate à fraude e evasão fiscais - Lopes, Carla Alexandra Loureiro (2022)
The main objective of the study was to verify to what extent the audit procedures adopted by Tax and Customs Authority are effective and contribute to the fight against tax fraud and evasion. Thus, the following question was asked: "To what extent the financial audit procedures adopted by Tax and Customs Authority can contribute to combating tax fraud and evasion", which served as a guiding thread for research. The financial audit began between the 15th and 16th centuries, is considered an asset to the entities given the increased reliability of the financial report disclosed and has as main normative reference the ISA. The tax audit made by Tax and Customs Authority aims to verify the correct declaration of taxes by taxpayers, this has as main normative reference the RCPITA. The objective of Financial Audit is included in the tax inspection. The study methodology was based on an empirical study focused on the central issue, supported by interviews with experts in the private and public tax areas, with the objective of comparing the technical and human means available to tax auditors integrated in Companies of Statutory Auditors. The use of ISA based procedures and techniques of financial auditing are a viable means in combating tax fraud and evasion, however its effectiveness is limited to specific cases. The contribution of ISA as a normative reference for the allocation of resources in tax inspections is recognized but does not cancel the efficiency of the RCPITA.